Prevention of malalignment during non-reversed femorodistal bypass. - Davies, A. H. (Royal College of Surgeons of England, 1992)
A simple technique is described using a Doppler flowmeter to prevent malalignment of a vein graft during femorodistal reconstruction. In 63 non-reversed vein bypass grafts, this technique has been used and no evidence of malalignment has been found on subsequent completion arteriography.